Deterring Cheating Using a Complex Assessment Design - Bjelobaba , Sonja (Canadian Perspectives on Academic Integrity, 2021)
Attempts to translate written examination normally done in a lecture hall to an online environment during an emergency remote learning caused by Covid-19 have not been proved successful, but led to a sharp increase of cases of suspected misconduct. This presentation is based on the paper (Bjelobaba, 2021) that discusses the relationship between assessments design and academic integrity: is it possible to deter students from cheating – including contract cheating – by assessment design? Previous research does promote certain assessment types, but also points that there is no single assessment type that students think is impossible to cheat on. The solution proposed in this paper, therefore, is to add complexity to the mixture. An alternative complex assessment design in several steps is introduced and exemplified by an assessment type piloted in a grammar course for preservice language teachers in Mother Tongue Tuition. The assessment design promotes academic integrity, signature pedagogy, student-centred learning, and collaboration within a Community of practice in an online setting.